Early Childhood Development: Wealth, the Nurturing Environment and Inequality First Results from the PRIDI Database - Aimee Verdisco; Santiago Cueto; Jennelle Thompson (Inter-American Development Bank (IDB), 2016)
This paper presents findings from the Regional Project on Child Development Indicators, PRIDI for its acronym in Spanish. PRIDI created a new tool, the Engle Scale, for evaluating development in children aged 24 to 59 months in four domains: cognition, language and communication, socio-emotional and motor skills. It also captures and identifies factors associated with child development. The Engle Scale was applied in nationally representative samples in four Latin American countries: Costa Rica, Nicaragua, Paraguay and Peru. The results presented here are descriptive, but they offer new insight regarding the complexity of child development in Latin America. The basic message emerging from this study is that child development in Latin America is unequal. Inequality in results appears as early as 24 months and increases with age. There is variation in inequality. For example, correlations with the socio-economic characteristics of the home and maternal education are stronger for cognition, and language and communication than for motor development. The environment within which children develop and the adult-child interactions predominant within this environment - referred to in this study as the nurturing environment - is important for all domains of child development utilized in this study, although stronger associations appear for cognition, language and communication, and socio-emotional development. For all domains measured by the Engle Scale, the nurturing environment bears a statistically stronger correlation than the socio-economic endowment of the home or maternal education. Gaps between the development of children in the top and low extremes in these factors matter. By 59 months, the development of a poor and under-nurtured child will lag by as much as 18 months behind her richer and more nurtured peers. For this child it will be more difficult to recognize basic shapes like triangles or squares, count to 20, or understand temporal sequences. She will also have gaps in her basic executive functioning and socio-emotional skills, including empathy and autonomy. She will not likely be ready for school and may not have success once there. Notably, however, if this same child, in the same poor household, were to benefit from a nurturing environment, her level of development would rise and would start to approach levels found in children in richer but less nurtured households. The nurturing environment thus appears to mitigate the negative association lower levels of wealth have with the domains of development included in this study.
hdl:11319/7788
Keywords: O2; I20; I21; I30; N76; 330; Child development; Children; Social conditions; Children and the environment; Latin America